The Role of Islamic Education Teachers and Classroom Teachers in Addressing Bullying: A Case Study at SDN 1 Pulosaren - Utami, Yeni Sabrina; Taufiq Fauzan Ginanjar (The Future of Education Journal, 2026)
Bullying is a serious problem in elementary schools that negatively affects students’ psychological and social development, often occurring in verbal and social forms that are difficult to detect. This study aims to describe the roles of Islamic Education (PAI) teachers and classroom teachers in addressing bullying at SDN 1 Pulosaren. This research employed a qualitative approach using a case study method. The population included PAI teachers, classroom teachers, the school principal, and students involved in bullying cases, with purposive sampling based on direct involvement in the phenomenon. Data were collected through observation guidelines, in-depth interviews, and documentation. The data were analyzed using the Miles and Huberman model, which includes data reduction, data display, and data verification. The findings indicate that PAI teachers instill moral values through religious instruction, while classroom teachers conduct daily supervision and apply persuasive approaches. The collaboration between both teachers has proven effective in reducing verbal and social bullying. It is concluded that the synergy between teachers’ roles contributes to creating a safe school environment. Therefore, collaborative training programs and greater parental involvement are recommended.